Quality of survival assessment in European childhood brain tumour trials, for children aged 5 years and over. (March 2015) - Limond, Jennifer A.; Bull, Kim S.; Calaminus, Gabriele; Kennedy, Colin R.; Spoudeas, Helen A.; Chevignard, Mathilde P.
Abstract: Introduction: There is increasing recognition of the long-term sequelae of brain tumours treated in childhood. Five year survival rates now exceed 75% and assessing the quality of survival (QoS) in multiple domains is essential to any comparison of the benefits and harms of treatment regimens. Aim: The aim of this position statement is to rationalise assessments and facilitate collection of a common data set across Europe. Sufficient numbers of observations can then be made to enable reliable comparisons between outcomes following different tumour types and treatments. Methods: This paper represents the consensus view of the QoS working group of the Brain Tumour group of the European Society of Paediatric Oncology regarding domains of QoS to prioritise for assessment in clinical trials. This consensus between clinicians and researchers across Europe has been arrived at by discussion and collaboration over the last eight years. Results: Areas of assessment discussed include core medical domains (e.g. vision, hearing, mobility, endocrine), emotion, behaviour, adaptive behaviour and cognitive functioning. Conclusions: A 'core plus' approach is suggested in which core assessments (both direct and indirect tests) are recommended for all clinical trials. The core component is a relatively brief screening assessment that, in most countries, is a sub-component of routine clinical provision. The 'plus' components enable the addition of assessments which can be selected by individual countries and/or tumour-, age-, and location-specific groups. The implementation of a QoS protocol common to all European clinical studies of childhood brain tumours is also discussed